The impact of working capital management on the return on assets of e-commerce companies in Indonesia from 2022 to 2024 - Oktafiani, Fida (Institute of Computer Science (IOCS), 2025)
This research discusses how working capital management affects return on assets (ROA) among Indonesian e-commerce companies from 2022 to 2024. Effective working capital management is crucial for companies' sustainability and profitability, especially in the highly dynamic e-commerce sector, which requires a high level of liquidity. In this study, a quantitative method and secondary data are used to analyze three e-commerce companies that are listed on the Indonesia Stock Exchange (IDX). The data is taken from the annual financial reports of Indonesian e-commerce companies. The independent variables include the cash turnover, accounts receivable turnover, and inventory turnover ratios, as well as the trade debt-to-sales ratio, which are indicators of working capital management. ROA is used as the dependent variable to measure company profitability. The data was analyzed and the research hypotheses were tested with the help of panel data regression. The study's objective is to provide empirical evidence regarding the contribution of optimizing working capital components, such as cash management, accounts receivable, and inventory, to the profitability of e-commerce companies. However, the study revealed that there is no significant relationship between cash turnover, accounts receivable turnover, or inventory turnover and a company's ROA.